PENDIDIKAN KARAKTER PADA ANAK USIA DINI BERDASARKAN HADIS NABI SAW - Wafa Aerin (IAIN Purwokerto, 2020)
: Age 0 to 6 is an early age. This age is the golden age or the golden age. In this phase the child has the most optimal ability to absorb all the knowledge gained in the environment. So that the child's development and personality develop optimally, so in this phase the child should be given maximum stimulation too, one of which is the cultivation of character. Planting characters from an early age is the same as forming good character in children from an early age. In its implementation, the cultivation of character requires a process, example (example) and habituation or acculturation in the environment, starting from the family, school, community, and exposure environment (mass media). So, this study aims to understand the formulation of the concept of planting character education in the traditions of the Proph et SAW. Through a review of contextual understanding and revealing the relevance of the traditions of the Prophet SAW in the perspective of contemporary character education.